Analisis Determinan Pendapatan Pedagang Pasar Banjarsari Kota Pekalongan Pasca Kebakaran - Nur Elitami Insan; Arif Pujiyono (ECONBANK: Journal of Economics and Banking, 2020)
The income of traders in the Banjarsari Emergency Market Pekalongan is influenced by various factors, one of which is the trader resources (capital, working hours, business length, education, and business location). This study aims to determine the effect of capital, working hours, business length, education, and business location on the income of traders in the Banjarsari Emergency Market in Pekalongan. There as 95 traders of Banjarsari Emergency Market in Pekalongan were taken as samples with purposive sampling and accidental sampling. This study uses multiple linear regression analysis tools with the Ordinary Least Square (OLS) method. The results showed that capital, length of business, and location of business affect the income of traders. While working hours and education have not affect the income of trader. Capital provides the most dominant influence on income trader